(untitled) (The Research of Medical Science Review, 2025)
Background: Most surgical procedures are usually carried out with the help of anesthesia. Two main types of anesthesia are frequently employed: general anesthesia (GA) and regional anesthesia (RA). However, there is a lack of documented data regarding regional anesthesia in our country. Our study indicates that a significant number of patients choose general anesthesia (GA), primarily due to a lack of awareness about the benefits associated with regional anesthesia (RA). Objectives of the Study: To evaluate the frequency of patient refusal and associated factors for ’Regional Anesthesia’ in the adult population at Lady Reading Hospital in Peshawar, Khyber Pakhtunkhwa (KPK). Materials and Methods: A cross-sectional study was conducted at Lady Reading Hospital (LRH) in Peshawar, Khyber Pakhtunkhwa (KPK), following the necessary permissions and approval from the hospital’s ethical board. Our study included a total sample size of 190 participants. Analysis of data was performed by utilizing the SPSS (version 22.0). Results: In this study, 61.1% of patients were aware of regional anesthesia, while 38.4% were unaware. Our study revealed that two major factors were responsible for refusal of regional anesthesia. The most significant factor was the negative perception being heard about regional anesthesia with a (P value of 0.00) while the other factor was the patient’s concern being awake (P= 0.028) during the procedure. Conclusion: Our observation found a notable choice for general anesthesia (GA) instead of regional anesthesia among patients. The primary reason for this choice was their concern about regaining consciousness during the surgical procedure. Secondly, negative perceptions about regional anesthesia that they had heard significantly influenced their decision.